Currency crises: Is Asia different? - Markus Diehl; Rainer Schweickert (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
International investors' enthusiasm with respect to growth prospects in Southeast Asia has been followed by panic. Both the outstanding economic performance of Southeast Asian economies and their ability to master adjustment challenges had led most observers of these economies to the conclusion that "Asia is different". In comparison with previous currency crises, the macroeconomic fundamentals (GDP growth, inflation, fiscal deficit, external indebtedness, domestic savings, export performance) in the Southeast Asian economies seemed to be consistent with the fixed or quasi-fixed exchange rate regimes. Even large current account deficits were not classified as "high risk" although the vulnerability of Southeast Asian countries had increased during the last decade due to a surge in capital inflows, a construction boom, the appreciation of the US dollar, and the liberalization of domestic financial markets without strict enforcement of prudential standards. Early signals of vulnerability should have warned domestic policymakers to take precautionary measures such as more exchange rate flexibility to end sterilization policies, higher marginal reserve requirements, and prudential standards for bank lending to reduce the risk exposure of banks. Some of these measures were taken in 1996, but apparently it was too little or too late. In the aftermath of the crisis, the enforcement of prudential rules in the financial sector and the clearing of bad debt figure high on the policy agenda. In order to help financial restructuring, fiscal and monetary policies should not be overly restrictive. The role of external assistance is ambiguous because of negative incentive effects. The currency crises in Asia boosted the amounts of emergency lending by the IMF and other countries, which may raise expectations that defaults will become cheaper in the future. Moreover, officially implemented early warning systems may easily produce the bad news which triggers exchange rate crises. All in all, Asia is not different from other regions. High current account deficits and real appreciation expose countries with fixed or quasi-fixed exchange rates and fragile domestic financial markets to the risk of a reversal of capital inflows. This mounting risk position can lead to a crisis when bad news arrives and domestic measures are delayed. Therefore, Asia could have learned from previous currency crises in Latin America and Europe: first, extreme solutions for the exchange rate regime (currency boards or a passive crawling peg with wide intervention bands) work best; second, deregulated goods and factor markets with strict prudential supervision (especially in the phase of financial liberalization) are necessary preconditions for a stable fixed exchange rate regime; third, development models with discretionary government interventions face difficult times since the globalization of goods and factor markets renders economic plans of today obsolete tomorrow.
Keywords: 330; Währungskrise; Fester Wechselkurs; Aufwertung; Zahlungsbilanzungleichgewicht; Geldpolitik; Bankenkrise; Internationale Kapitalmobilität; Südostasien; Indonesien